Schiller and Music - Longyear, R.M (UNC Studies in the Germanic Languages and Literatures, 1966)
In this first definitive study of Friedrich Schiller's relationship to music, R. M. Longyear discusses Schiller's personal, literary, and philosophical utilization of music as well as the influence of Schiller's works on composers from 1782 through the 1960s.